From Performance to Participation: The Origins of the Fit Nation - Natalia Mehlman Petrzela (Transatlantica)
Though only one-fifth of Americans do the recommended amount of daily physical exercise and most measures point to an extraordinary lack of fitness in the United States, the pursuit of regular exercise is widely celebrated not only as physically salutary, but as a sign of discipline, affluence, and virtue. Using popular press, institutional records, advice literature, advertisement, and memoir, this article explains how this was not always so. The pursuit of exercise evolved from a strange, suspicious subculture characterized by individual performance in the late nineteenth and early twentieth centuries to a more participatory realm represented by Muscle Beach in the 1940s and 1950s, establishing the foundation of today’s “fit nation,” a culture in which the pursuit of exercise is valorized as an ideal, but not equitably accessible.